Does gender or mode of HIV acquisition affect virological response to modern antiretroviral therapy (ART)?. Issue 1 (2nd July 2015) - Saunders, P; Goodman, AL; Smith, CJ; Marshall, N; O'Connor, JL; Lampe, FC; Johnson, MA
Abstract : Objectives: Previous UK studies have reported disparities in HIV treatment outcomes for women. We investigated whether these differences persist in the modern antiretroviral treatment (ART) era. Methods: A single‐centre cohort analysis was carried out. We included in the study all previously ART‐naïve individuals at our clinic starting triple ART from 1 January 2006 onwards with at least one follow‐up viral load (VL). Time to viral suppression (VS; first viral load < 50 HIV‐1 RNA copies/mL), virological failure (VF; first of two consecutive VLs > 200 copies/mL more than 6 months post‐ART) and treatment modification were estimated using standard survival methods. Results: Of 1086 individuals, 563 (52%) were men whose risk for HIV acquisition was sex with other men (MSM), 207 (19%) were men whose risk for HIV acquisition was sex with women (MSW) and 316 (29%) were women. Median pre‐ART CD4 count and time since HIV diagnosis in these groups were 298, 215 and 219 cells/μL, and 2.3, 0.3 and 0.3 years, respectively. Time to VS was comparable between groups, but women [adjusted hazard ratio (aHR) 2.32; 95% confidence interval (CI) 1.28–4.22] and MSW (aHR 3.28; 95% CI 1.91–5.64) were at considerably higher risk of VF than MSM. Treatment switches and complete discontinuation were also more common among MSW [aHR 1.38 (95% CI 1.04–1.81) and aHR 1.73 (95% CI 0.97–3.16), respectively] and women [aHR 1.87 (95% CI 1.43–2.46) and aHR 3.20 (95% CI 2.03–5.03), respectively] than MSM. Conclusions: Although response rates were good in all groups, poorer virological outcomes for women and MSW have persisted into the modern ART era. Factors that might influence the differences include socioeconomic status and mental health disorders. Further interventions to ensure excellent response rates in women and MSW are required.